2021
DOI: 10.1186/s12876-021-01660-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomised placebo controlled trial of VSL#3® probiotic on biomarkers of cardiovascular risk and liver injury in non-alcoholic fatty liver disease

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is associated with increased cardiovascular risk irrespective of conventional risk factors. The role of gut-liver interaction is implicated in its development. We investigated the effects of VSL#3® probiotic supplementation on biomarkers of cardiovascular risk and liver injury in patients with NAFLD. Methods A randomised, double-blinded, placebo-controlled, proof-of-concept study was undertaken. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
1
35
1
Order By: Relevance
“…In literature, a previous proof-of-concept study conducted on a little number of patients was undertaken showing that VSL#3 ® did not significantly improve the markers of cardiovascular risk and liver injury in patients with NAFLD after 10 weeks of treatment. However, the study supports an association between endothelial dysfunction and inflammation in patients with NAFLD ( 10 ). On this basis, we projected a larger and longer study aimed to evaluate if a supplementation with VSL#3 ® [a high-concentration multi-strain probiotic mix containing one strain of Streptococcus thermophilus BT01, three strains of Bifidobacteria ( B. breve BB02; B. animalis subspecies [subsp.]…”
Section: Introductionsupporting
confidence: 63%
“…In literature, a previous proof-of-concept study conducted on a little number of patients was undertaken showing that VSL#3 ® did not significantly improve the markers of cardiovascular risk and liver injury in patients with NAFLD after 10 weeks of treatment. However, the study supports an association between endothelial dysfunction and inflammation in patients with NAFLD ( 10 ). On this basis, we projected a larger and longer study aimed to evaluate if a supplementation with VSL#3 ® [a high-concentration multi-strain probiotic mix containing one strain of Streptococcus thermophilus BT01, three strains of Bifidobacteria ( B. breve BB02; B. animalis subspecies [subsp.]…”
Section: Introductionsupporting
confidence: 63%
“…In addition, similar hepatoprotective effects were also described in a study in which probiotics were administered mixed in a yogurt, instead as a supplement (capsule or sachet) [ 59 ]. Nevertheless, there are also studies in which the administration of probiotics did not result in the improvement of markers of liver injury in patients with NAFLD, despite the fact that the doses used and the administration periods were similar to those studies in which significant improvements were reported ( Table 3 ) [ 60 , 61 ]. In this regard, according to Mohamed Nor et al [ 60 ], the reduced sample size, along with the apparent higher variability of Malaysians’ gut microbiota composition (due to a more diverse dietary intake), may have influenced the obtained results.…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 80%
“…Nevertheless, there are also studies in which the administration of probiotics did not result in the improvement of markers of liver injury in patients with NAFLD, despite the fact that the doses used and the administration periods were similar to those studies in which significant improvements were reported ( Table 3 ) [ 60 , 61 ]. In this regard, according to Mohamed Nor et al [ 60 ], the reduced sample size, along with the apparent higher variability of Malaysians’ gut microbiota composition (due to a more diverse dietary intake), may have influenced the obtained results. Moreover, the authors also pointed to a change in dietary fat observed in the group receiving the probiotic, which could have somehow blunted the potential beneficial effects of the probiotic intervention [ 60 ].…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 80%
See 1 more Smart Citation
“…It did not appear to improve cardiovascular risk factors and liver injury scores. Nevertheless, it improved HOMA-IR (Chong et al, 2021). Another randomized controlled cross-over study showed that metabolic syndrome symptoms were not alleviated by a daily intervention with Lactobacillus reuteri V3401 strain for 12 weeks.…”
Section: 1probioticsmentioning
confidence: 99%